Time sampling effects on UV daily doses derived from satellite data - Bugliaro, Luca; Meerkötter, Ralf (2003)
The determination of ultraviolet daily doses from satellite data is a very helpful method for investigating the biological impact of UV radiation on biological species over wide areas. To achieve this aim, geostationary or polar orbiting satellites can be used, as was done for instance in the EU project UVAC. There, two distinct climatologies of UV radiation were produced, one based on the Meteosat and one on the NOAA satellites for the derivation of cloud optical properties. Geostationary satellites allow in principle to probe the cloud fields many times a day, thus better accounting for the diurnal cycle of the varying clouds than polar orbiting satellites. However, in Northern latitudes their spatial resolution is significantly reduced compared to that of polar orbiting satellites. Furthermore, considering the high demands on cpu and processing times as well as on disk space, the problem of finding a reasonable compromise between number of cloud probes per day and accuracy naturally arises. To address this question we simulate the surface UV radiation for different diurnal cycles of cloud fields by means of the 3- dimensional radiative transfer code SHDOM. The results illustrate how the accuracy in computing UV daily doses depends on the number of cloud probes and the smoothing effects due to temporal and spatial variability. We further compare model results obtained for the typical temporal sampling of the NOAA and Meteosat satellites and show the importance of sampling around noon time. Herewith, this study, that has been performed in the framework of UVAC, may represent a basic tool for evaluating every satellite based climatology.